Analysis of Vocabulary Material in "Bahasa Inggris Kelas XI" (KemenDikBud) Textbook - Simatupang, Norris S E (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Textbook is one of the form of teaching material and a significant guide for teachers and students. One of the factors determining student success in learning activity is the quality of the textbook. Learning vocabulary plays a vital role in all language skills such as listening, speaking, reading, and writing. Thus the author decided to analyze the vocabulary materials in Bahasa Inggris Kelas XI textbook published by the Ministry of Education and Culture of the Republic of Indonesia. This analysis needs to be done to prove whether or not this textbook has sufficient quality to develop students' vocabulary. This research will be conducted using a qualitative research approach. The data collection method uses descriptive method because the author focuses on the vocabulary material in each chapter of the textbook. The data is analyzed using the instrument of textbook assessment by Houtz elements (1955). The results of the analysis that has been carried out shows that the textbook is suitable to be used as teaching material for the learning process in schools.